Transferências governamentais: uma análise de seu impacto no comportamento orçamentário dos municípios brasileiros - Alves, Pedro Jorge Holanda (2020)
The objective of this work is to analyze the impact of fiscal decentralization on the actions of Brazilian municipal policy makers. The work uses the first three textit cutoffs of the transfer rules of the Municipal Participation Fund (FPM) and applies a Discontinuous Regression (RDD) model to capture the effects of these transfers on the municipal budget during the years of 2013 to 2016. The expected from the results are the reflections that the gains from transfers can generate: (i) perverse incentives, if the gains are destined to personnel and administrative expenses or decrease own revenues; or (ii) beneficial incentives if the main gains are spent on education or health. The results found for the panel select that the increase in revenue generated generates a significant increase in spending only in the administrative function, which records as transfers generated only perverse incentives. Spending on sports and leisure also showed discontinuity, however, due to low value in the municipal budget, this discontinuity was very small. There is no longer spending on education and health, but there is no discontinuity, so there are no incentives for transfers to increase this spending.